Analisis Perbandingan Metode Westergrand Terhadap Metode Desain Langsung Dan Metode Portal Ekivalen Pada Flat Plate - Ramadhan, Rian; Djauhari, Zulfikar; Kurniawandy, Alex (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
All this time the analysis and design of plate is often done by using approach method such as Westergrand that commonly used and also use the Direct Design methods and EquivalentFrame methods, this approach method is more often used because it is very difficult to plan a plate with using numerical methods such as finite element method although the results will be more exact. This study aims to determine the comparison between Westergrand method, Direct Design method and Equivalent Frame method, espe cially when applied to the plates that do not have beams such as Flat Plate. This comparison is done in order to see how good this method in terms of ease of calculation, the results of moments, reinforcement and deflection result and in order to see how the behavior of Flat Plate when analyzed using these methods.This research results showed Westergrand method have easier calculation methods when compared to the Direct Design method and Equivalent Frame method but Westergrand method will give a smaller value than the Direct Design method and Equivalent Frame method in terms of moments, reinforcement and deflection. Based on the research results that higher the ratio between long span and short span, the plate behavior will be getting closer to the of one wayaction and corner panel receive the largest proportion of the load from interior and exterior panels.Keyword Plate, Westergrand Method, Direct Design Method, Equivalent Frame Method